2014
DOI: 10.1002/anie.201405008
|View full text |Cite
|
Sign up to set email alerts
|

gem‐Difluorocarbadisaccharides: Restoring the exo‐Anomeric Effect

Abstract: Molecular mimicry is an essential part of the development of drugs and molecular probes. In the chemical glycobiology field, although many glycomimetics have been developed in the past years, it has been considered that many failures in their use are related to the lack of the anomeric effects in these analogues. Additionally, the origin of the anomeric effects is still the subject of virulent scientific debates. Herein, by combining chemical synthesis, NMR methods, and theoretical calculations, we show that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 36 publications
3
43
0
1
Order By: Relevance
“…Additionally,o nly in the presence of fluorine atoms at C5a, the Ido-like six-membered ring recovers its requiredf lexibility,a bsent in regularC H 2 -Ido-carbasugars, [38] while the presence of ab ulky substituent at positionC 5s trongly reduces the ring flexibility and introduces important steric clashes. Ar ecent report from our group [20] has shown that the CF 2 moiety partially recovers the exo-anomericeffect typical of oligosaccharides, thus resembling the conformational behaviour of glycans around the glycosidic linkage. Herein, we also demonstrate that the presence of the fluorine in the ring additionally restores the plasticity of Ido-likesix-memberedr ings.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Additionally,o nly in the presence of fluorine atoms at C5a, the Ido-like six-membered ring recovers its requiredf lexibility,a bsent in regularC H 2 -Ido-carbasugars, [38] while the presence of ab ulky substituent at positionC 5s trongly reduces the ring flexibility and introduces important steric clashes. Ar ecent report from our group [20] has shown that the CF 2 moiety partially recovers the exo-anomericeffect typical of oligosaccharides, thus resembling the conformational behaviour of glycans around the glycosidic linkage. Herein, we also demonstrate that the presence of the fluorine in the ring additionally restores the plasticity of Ido-likesix-memberedr ings.…”
Section: Discussionmentioning
confidence: 77%
“…[17] In this context, difluorinated carbasugars have been recently synthesized. [18][19][20] Their suitability to act as improved sugar analogues has been studied.I ndeed, the presence of fluorine atoms emulates, toac ertain degree, the properties of the endocyclic oxygen [20] and, consequently,t hey are betterc andidates to mimic naturalg lycans than their non-fluorinated analogues. The possibility of the presence of intramolecular OHÀF hydrogen bonds should also be explored, along with their structural and conformational implications.…”
Section: Introductionmentioning
confidence: 99%
“…86 Trifluoromethylated and polyfluorinated lipids have also been exploited either as direct substrates of lipid-and glycolipid modifying enzymes. 93 Although it has been recently shown than a CF 2 moiety at the pyranose ring may restore the key exo-anomeric effect, 94 to the best of our knowledge, the structural basis to justify the replacement of a carbohydrate vicinal diol for a polyfluorinated system in molecular recognition events has never been reported to date. These observations, along with the discovery of the hexafuranose binding mode to UGM, should now provide the impetus for the development of yet more potent inhibitors.…”
Section: 87mentioning
confidence: 99%
“…gave the corresponding 5-iodo 7 (29%) and the α-fluorothioether 8 (12%) products (Scheme 2). Analogous treatment of sulfide 6 with NIS/DAST combination 53,54 produced the mono-α-fluorothioether 8 in 44% isolated yield without 5-halogenation. In contrast, treatment of 6 with DBH (3 eq.…”
Section: Resultsmentioning
confidence: 99%